A Study of Nucleotide Binding Domain of Glycerol Kinase Gene from Aloe vera - Suvarna, Sharma; Sharon, K (International Journal of Scientific Research in Biological Sciences, 2019)
Aloe vera, belonging to family Liliaceae, is a monocot and used also for medicinal purpose. They are succulent and retain large amount of water in their leaves. In the recent decade few genes from Aloe vera have been elucidated, some being stress inducible. Glycerol kinase is the enzyme involved in the first step of Glycerol metabolism. In order to study the gene, its nucleotide binding domain was targeted by PCR approach. A 256bp long amplification product was obtained which on sequencing and in- silico analysis confirmed to be NBD domain of Glycerol kinase. This domain belongs to the superfamily NBD_ Sugar kinase_HSP70_Actin, which all harbor the same conserved domain. It shows 52% alignment with the FGGY C- Terminal region of Escherichia coli, which also harbor sites for ATP binding. This paper confirms the presence and studies the structure of the NBD domain, thereby indicating the presence of a glycerol kinase gene in Aloe vera genome for the first time.